Babysitters Club :Boy-crazy Stacey. #7. 07 - Galligan, Gale; Martin, Ann M., 1955- (New York, NY : Graphix, an imprint of Scholastic, 2019)
Accompanying the Pike family during a two-week vacation to the Jersey Shore, baby-sitter Stacey falls head over heels for a handsome lifeguard despite Mary Anne's warning that he is too old for her.
"Based on the novel by Ann M. Martin"--Cover.
Chiefly illustrations.
GN580L
Keywords: Babysitters -- Juvenile fiction; Graphic novels -- Juvenile fiction; Lifeguards -- Juvenile fiction; Summer employment -- Juvenile fiction